Selection of housekeeping genes for quantitative gene expression analysis in yellow-feathered broilers - Zhang, Jie; Gao, Yu-Yun; Huang, Yi-Qiang; Fan, Qian; Lu, Xin-Tao; Wang, Chang-Kang (Italian journal of animal science, 2018)
The aim of this study was designed to select housekeeping genes for quantitative gene expression analysis in yellow-feathered broilers. Twelve 3-week-old chickens were randomly selected from 60 yellow-feathered broilers. Then, 12 chickens were killed; the liver and jejunum samples were collected. The gene expression of housekeeping genes (β-actin, ACTB; glyceraldehyde-3-phosphate dehydrogenase, GAPDH; hypoxanthine phosphoribosyl transferase 1, HPRT1; ribosomal protein L13, RPL13; TATA box binding protein, TBP; hydroxymethylbilane synthase, HMBS) were determined using quantitative real-time reverse transcriptase polymerase chain reaction (RT-PCR). Furthermore, the expression stabilities of housekeeping genes were analysed using geNorm, Normfinder and BestKeeper programs. The result showed that RPL13 is the most proper gene in liver, GADPH is the most proper gene in jejunum, and HMBS is the most proper gene in all tissues. In conclusion, this result provides the integrated reported evaluation of housekeeping genes for use in expression studies in yellow-feathered broilers. These findings further emphasise the need to accurately validate candidate housekeeping genes in the study before use in gene expression studies using RT-PCR.